Letter - Hargreaves, C.
034-0041-001 Mr Carthy 646 Nelson & District Weavers' Association. TEL 97 NELSON SECRETARY: C. HARGREAVES, PENDLE STREET, NELSON. 8/4/1942 To the General Secretary Trades Union Congress Transport House Smith Square London Dear Comrade. We would urge the T.U.C. to give what aid it can in response to the request of the International Brigade Association as contained in the enclosed letter. If anything we can do as a movement can save these men from the Gestapo & kindred organisations we should make the effort. Please take action wherever the opportunity can be made so that nothing we can do shall be lacking. Yours faithfully C. Hargreaves Secretary 292/946/34/41